Toxicity of iron-based nanoparticles to green algae: Effects of particle size, crystal phase, oxidation state and environmental aging. (November 2016) - Lei, Cheng; Zhang, Luqing; Yang, Kun; Zhu, Lizhong; Lin, Daohui
Abstract: With the increasing environmental application and discharge of iron-based nanoparticles (NPs), a comprehensive understanding of their fate and ecotoxicological effect in the aquatic environment is very urgent. In this study, toxicities of 4 zero-valent iron NPs (nZVI) of different sizes, 2 Fe2 O3 NPs of different crystal phases, and 1 type of Fe3 O4 NPs to a green alga ( Chlorella pyrenoidosa ) were investigated, with a focus on the effects of particle size, crystal phase, oxidation state, and environmental aging. Results show that the algal growth inhibition of nZVI increased significantly with decreasing particle size; with similar particle sizes (20–30 nm), the algal growth inhibition decreased with oxidation of the NPs with an order of nZVI > Fe3 O4 NPs > Fe2 O3 NPs, and α-Fe2 O3 NPs presented significantly higher toxicity than γ-Fe2 O3 NPs. The NP-induced oxidative stress was the main toxic mechanism, which could explain the difference in algal toxicity of the NPs. The NP-cell heteroagglomeration and physical interactions also contributed to the nanotoxicity, whereas the effect of NP dissolution was negligible. The aging in distilled water and 3 surface water samples for 3 months increased surface oxidation of the iron-based NPs especially nZVI, which decreased the toxicity to algae. These findings will be helpful for the understanding of the fate and toxicity of iron-based NPs in the aquatic environment. Graphical abstract: Highlights: The algal toxicity of nZVI decreased with increasing particle size. α-Fe2 O3 NPs exhibited higher algal toxicity than γ-Fe2 O3 NPs. The iron-based NPs with higher oxidation presented lower algal toxicity. The aging in the water samples increased surface oxidation of nZVI. The aging in the water samples mitigated algal toxicity of iron-based NPs. Abstract : The algal toxicity of nZVI decreased with increasing particle size, surface oxidation, and environmental aging.